(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The study aimed to investigate the bioactivity effect of different concentration of ethanol Iraqi propolis against two species of bacteria. Staph.aureus and pseudomonas that were infected wound in skin of mice ,Results revealed that the concentration of 4000 and 5000 µg/ml of Iraqi propolis extracted by 75% ethanol was the most effective in growth inhibition of Staph.aureus and pseudomonas in agar diffusion method and the diameter of inhibition in Staph.aureus reached (22.30, 22.50), mm. respectively, while the diameter of inhibition of pseudomonas in a concentration of 4000 and 5000 µg/ml was (21.12,23 .60) mm. by the agar diffusion method as shown propolis was highly effective against Staph.aureus and pseudomonas in agar diffusion method with comparing the antibiotic Amoxicillin 30µg with different concentration of ethanol extract of the Iraqi propolis showed no inhibition of the Ampicillin30µg, Methoprim 25 and gentamycin 100 µg against Staph.aureus and pseudomonas. The previous concentration (4000,5000) was also superior in comparing with Ordinary ointment in terms of its effect on the healing of contaminated and non-contaminated wounds, as well as the return of the tissue to its normal position in a shorter time. where The propolis extract showed a high potency in treating wounds infected with Gramnegative (pseudomonas) and Gram-positive bacteria(Staph.aureus).